Desenvolvimento e avaliação de hidrogel baseado em poloxamer- quitosana contendo eugenol para aplicação na mucosa bucal - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The drugs actions may be improved through the development of release systems, like the mucoadhesive system. These systems keep touching near the absorption tissue, the mucous membrane, releasing the drug to the site of action. The hydrogel has been extensively studied due to its properties of the swelling kinetics control. The chitosan is a byopolimer with mucoadhesive property, which is suitable for administration through the mucous, besides, it is not inactived When contacts the mucin and its mucoadhesion does not decrease during the time. Thus, the use of in situ gelation of hydrogels with mucoadhesive properties as releases system of substances by buccal route is an important strategy in treatments of affections and others procedures in buccal cavity. Eugenol, with anestesic properties, associated to new release systems for the treatment of buccal inflamation, as well as its topicais use in periodontal diseases has been extensively studied. This study aimed to develop and evaluate a hydrogel based on polomaxer-chitosan containing eugenol for application to the buccal mucosa to optimize its anestesic properties. Five experimental groups were determined: poloxamer hydrogel (PH), poloxamer-chitosan hydrogel (PCH), poloxamer-chitosan hydrogel with 1% w/w eugenol (PCHEU1), poloxamer-chitosan hydrogel with 2% w/w eugenol (PCHEU2), poloxamer-chitosan hydrogel with 4% w/w eugenol (PCHEU4). The physico-chemical characterization was carried out by determination of the sol-gel transition by the tube inversion method; determination of pH, turbidimetric evaluation, determination of scatterability, texture profile, quantification of the drug by UV-vis spectrophotometry and determination of the rheological profile of the hydrogels. Stability study utilized pH and turbidity evaluations and quantification of the drug. The mucoadhesive property was studied with ex vivo model in pig cheek. The sol / gel transition determination demonstrated that the PCHEU1 and PCHEU2 formulations were suitable with transition temperatures of 25.33 ±0.57 °C and, 19.33 ±0.57 °C, respectively, however for PCHEU4, it was not possible to determinate. The texture profile and scatterability analysis presented acceptable values for the totality of formulations, with better results for PCHEU1 and PCHEU2. Stability study allowed establishing more adequate storage criteria, being more favorable at 5 ±2 ºC. The rheological profile of the formulations showed favorable values for the elastic behavior, wich contributes to retention at the application site as well as to the eugenol release in the buccal mucosa. The mucoadhesion test showed that the PCHEU1, PCHEU2 and PCHEU4 formulations are able to adhere to the mucosa, being the PCHEU4 with the highest mucoadhesive ability. Considering all the analysis for the hydrogels containing eugenol, none of the studied formulations covered, satisfactorily, all the properties, however, the PCHEU1 formulation had the closet profile related with application with intermediate mucoadhesive properties as well as the rheological profile, followed by the PCHEU2 hydrogel. Therefore, the hydrogels containig eugenol are suggested as formulations, with thermoresponsive nature, for buccal mucosa with the ability of sustained release to be used with dentistry application.
Keywords: Cavidade bucal; Poloxâmeros; Anestésico; Biopolímeros; Buccal cavity; Poloxamers; Anesthetic; Biopolymer; CNPQ::CIENCIAS DA SAUDE::FARMACIA